2016
DOI: 10.1111/desc.12435
|View full text |Cite
|
Sign up to set email alerts
|

Children on the autism spectrum update their behaviour in response to a volatile environment

Abstract: Typical adults can track reward probabilities across trials to estimate the volatility of the environment and use this information to modify their learning rate (Behrens et al., 2007). In a stable environment, it is advantageous to take account of outcomes over many trials, whereas in a volatile environment, recent experience should be more strongly weighted than distant experience. Recent predictive coding accounts of autism propose that autistic individuals will demonstrate atypical updating of their behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
79
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 54 publications
13
79
1
Order By: Relevance
“…However, it is worth mentioning that other studies have shown that ASD children are able to use statistical information from the environment to a similar extent as TD children. For instance, Manning et al [51] tested how ASD and TD children used reward probabilities in a decision-making task under stable or volatile contexts (i.e. fixed versus fluctuating probabilities).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is worth mentioning that other studies have shown that ASD children are able to use statistical information from the environment to a similar extent as TD children. For instance, Manning et al [51] tested how ASD and TD children used reward probabilities in a decision-making task under stable or volatile contexts (i.e. fixed versus fluctuating probabilities).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Manning et al [51] also explored the possible link between children's anxiety and task performance. However, they did not find correlations between these aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, as for many other aspects of the ASD phenotype and pathology, there is yet no clear consensus. Remarkably, both attenuated Noel et al, 2016) and intact (Pell et al, 2016;Croydon et al, 2017;Karvelis et al, 2018) priors have been reported, as well as normal (Manning et al, 2017) and abnormal Lieder et al, 2019) updating of these priors. These conflicting results may partially be due to a lack of quantification.…”
Section: Introductionmentioning
confidence: 91%
“…However, the direction of gaze priors 23 and the light---from---above priors 24 were found to be intact. Autistic children also demonstrated intact ability to update their priors in a volatile environment in a decision---making task 25 but a follow---up study in ASD adults showed that they overestimate volatility in a changing environment 26 .…”
Section: Introductionmentioning
confidence: 99%